INTEGRAL SOLUTIONS - Thirunavukarasu, P.; Sriram, S. (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
We obtain the non-trival integral solutions for quartic Diaphoptine equations with two variables is presented. A few numerical examples are given.